2011
DOI: 10.1542/peds.2010-2213
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Postnatal Weight Change, and Risk for High Blood Pressure Among Chinese Children

Abstract: Greater birth weight or postnatal weight gain was associated with increased childhood hypertension risk, suggesting that intrauterine growth and postnatal weight gain may have implications on health during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 26 publications
1
74
1
Order By: Relevance
“…Larger size at birth, typically assessed by birthweight, 6 and faster weight gain during the first two postnatal years are consistently associated with obesity in childhood and adulthood, 6, 7 with some 8, 9 investigations also showing relationships with higher BP. Yet, several issues remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Larger size at birth, typically assessed by birthweight, 6 and faster weight gain during the first two postnatal years are consistently associated with obesity in childhood and adulthood, 6, 7 with some 8, 9 investigations also showing relationships with higher BP. Yet, several issues remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…obesity, hypertension, type 2 diabetes, and dyslipidemia) [1]. It has also been suggested that the risk for later disturbances associated with birth size may be U-shaped [2], and some recent studies have shown an association between large birth size and later childhood obesity [3,4], the metabolic syndrome, type 2 diabetes [5,6], and hypertension [7]. Furthermore, as obesity tracks from childhood to adulthood [8], childhood obesity is a predictor of hypertension, dyslipidemia, and type 2 diabetes in adulthood [9], thus creating a major global health risk.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] These associations are less clear in non-Western populations, such as in China, South Korea, Brazil, Mexico, India, and Japan. [6][7][8][9][10][11] Observational studies are vulnerable to residual confounding, particularly in Western settings where low socioeconomic position (SEP) is usually associated with both low birth weight and higher blood pressure. Ischemic heart disease is more common among men than women, and so it might be expected that birth weight or postnatal growth might have stronger associations with blood pressure among men than women, although there is little evidence on this point.…”
mentioning
confidence: 99%